2021
DOI: 10.1101/2021.03.22.436458
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Computational Structure Prediction Provides a Plausible Mechanism for Electron Transfer by the Outer Membrane Protein Cyc2 fromAcidithiobacillus ferrooxidans

Abstract: Cyc2 is the key protein in the outer membrane of Acidithiobacillus ferrooxidans that mediates electron transfer between extracellular inorganic iron and the intracellular central metabolism. This cytochrome c is specific for iron and interacts with periplasmic proteins to complete a reversible electron transport chain. A structure of Cyc2 has not yet been characterized experimentally. Here we describe a structural model of Cyc2, and associated proteins, to highlight a plausible mechanism for the ferrous iron e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…Recently, a cultured-based study associated with transcriptomics assays also demonstrated that the cytochrome Cyc2 participates in the Fe(II) oxidation process [106]. Cyc2 is predicted to be a transmembrane beta barrel protein with an N-terminal cytochrome-like region [107]. S. lithotrophicus ES-1 contains three cyc2 genes that are adjacent to one another in the genome, and that are more expressed than mtoA in Fe(II)-citrate cultures.…”
Section: Extracellular Electron Transfer Processes Of Sideroxydans Li...mentioning
confidence: 99%
“…Recently, a cultured-based study associated with transcriptomics assays also demonstrated that the cytochrome Cyc2 participates in the Fe(II) oxidation process [106]. Cyc2 is predicted to be a transmembrane beta barrel protein with an N-terminal cytochrome-like region [107]. S. lithotrophicus ES-1 contains three cyc2 genes that are adjacent to one another in the genome, and that are more expressed than mtoA in Fe(II)-citrate cultures.…”
Section: Extracellular Electron Transfer Processes Of Sideroxydans Li...mentioning
confidence: 99%